Gastrointestinal hormones in short bowel syndrome. Peptide YY may be the 'colonic brake' to gastric emptying. Issue 2 (August 1996) - Nightingale, J M; Kamm, M A; van der Sijp, J R; Ghatei, M A; Bloom, S R; Lennard-Jones, J E
Abstract : BACKGROUND: Short bowel patients with a jejunostomy have large volume stomal outputs, which may in part be due to rapid gastric emptying of liquid. Short bowel patients with a preserved colon do not have such a high stool output and gastric emptying of liquid is normal. AIMS: To determine if differences in the gastric emptying rate between short bowel patients with and without a colon can be related to gastrointestinal hormone changes after a meal. SUBJECTS: Seven short bowel patients with no remaining colon (jejunal length 30-160 cm) and six with jejunum in continuity with a colon (jejunal length 25-75 cm), and 12 normal subjects. METHODS: The subjects all consumed a 640 kcal meal; blood samples were taken for 180 minutes for measurement of gastrointestinal hormones. RESULTS: Patients with a colon had high fasting peptide YY values (median 71 pmol/l with a colon; 11 pmol/l normal subjects, p < 0.005) with a normal postprandial rise, but those without a colon had a low fasting (median 7 pmol/l, p = 0.076) and a reduced postprandial peptide YY response (p < 0.050). Motilin values were high in some patients without a colon. In both patient groups fasting and postprandial gastrin and cholecystokinin values were high while neurotensin values were low. There were no differences between patient groups and normal subjects in enteroglucagon, pancreatic polypeptide, or somatostatin values. CONCLUSIONS: Low peptide YY values in short bowel patients without a colon may cause rapid gastric emptying of liquid. High values of peptide YY in short bowel patients with a retained colon may slow gastric emptying of liquid and contribute to the "colonic brake'.